1965
DOI: 10.1139/v65-053
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole Chemistry: Iv. The Preparation and Some Reactions of Brominated Pyrrole Derivatives

Abstract: IVIethyl 2-pyrrolecarboxylate and 2-pyrrolecarboxaldehyde have been brominated under a variety of conditions and the isomer ratios determined. The products have been identilied as the 4-bromo, 5-bromo, and 4,5-dibromo derivatives and their structures proved. I t has been sho~vn that the bromine group in these products is not easily displaced by nucleophiles although this has been accomplished with the cyanide ion. The bromine has been removed easily by catalytic hydrogenation.In our survey of the reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 11 publications
2
58
0
Order By: Relevance
“…For studying the structure-activity relationship of the pyrrole part of bromopyrrole alkaloids, brominated pyrrole-2-carboxylic acid derivatives were either purchased commercially (9, 14-17, 19-22) or synthesized (10-13, 18) following procedures previously described by Bailey et al (1971) and Anderson & Lee (1965). Structures of the compounds were determined by mass spectrometry and NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…For studying the structure-activity relationship of the pyrrole part of bromopyrrole alkaloids, brominated pyrrole-2-carboxylic acid derivatives were either purchased commercially (9, 14-17, 19-22) or synthesized (10-13, 18) following procedures previously described by Bailey et al (1971) and Anderson & Lee (1965). Structures of the compounds were determined by mass spectrometry and NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in the early days, the availability of such pyrrole derivatives was severely limited, although syntheses of several relatively stable iodinated pyrroles, for example 2,3,4,5-tetraiodopyrrole [222], as well as some other bromo-or iodopyrroles featuring additional electron-withdrawing substituents were described [223,224]. An early study on the bromination of methyl pyrrole-2-carboxylate and pyrrole-2-carboxaldehyde under various conditions clearly demonstrated that formation of mixtures containing several halogenation products is a common course of many of these reactions, thus illustrating yet another complicating factor [225]. The labile 1-chloropyrrole, generated in 65-72% yield by chlorination of pyrrole with NaOCl, was shown to rearrange readily to give mixtures containing several species, such as 2-choro-and 3-chloropyrrole, when subjected to acidic conditions or heated in methanol [226].…”
Section: Halogenationmentioning
confidence: 99%
“…The Pictet-Spengler reaction uses 2-acetyl-aminohistamine [8] and 4,5-dibromo-1-SEM-pyrrol-2-carb-aldehyde [9] synthesized in a two-step synthesis starting with the bromination of pyrrol-2-carbaldehyde 25,26 and protection with trimethylsilylethoxymethyl chloride (SEMCl) 15. . This protecting group revealed itself as the most stable during the subsequent reactions steps and makes the chromatographic procedures easier, compared to the Boc-group.…”
Section: Introductionmentioning
confidence: 99%